Disseminated Coccidioidomycosis Presenting as Fever of Unknown Origin and Erythema Nodosum in a 3-Year-Old Child. (15th October 2021) - Mills, Lauren; Randall, Melanie M.
Abstract : Disseminated coccidioidomycosis is a disease caused by Coccidioides species, fungi endemic to the southwestern United States. We present here an uncommon case of a young child with erythema nodosum and fever of unknown origin, found to have the infection. While more common in adults, coccidioidomycosis should be considered in all patients with erythema nodosum.